Physicochemical and Organoleptic Properties of Milkfish Bonggolan (Study Proportion of Fish Meat : Sago Flour and Addition of Sodium tripolyposphate) - Amaliyah, Nur Azzatul; Rosida, Rosida; Priyanto, Anugerah Dany (Universitas Brawijaya, 2024)
Bonggolan is a fish product from the Sidayu, Gresik Regency. Bonggolan is made from a mixture of tapioca flour, fish meat, such as payus fish and spices. Bonggolan has a chewy texture with a savory taste and has a special aroma from fish. Bonggolan has a hard texture when consumed in cold condition. This change causes a decrease in consumer preference. In this study, learned about making bonggolan from milkfish meat, sago flour, and sodium tripolyposphate (STPP). The purpose of the study is to determine the effect of the proportion of fish meat : sago flour and the addition of STPP on the physicochemical and organoleptic properties of milkfish bonggolan. This study used a factorial Completely Randomized Design (CRD) with two factors. The first factor is the proportion of fish meat : sago flour (60 : 40, 50 : 50, 40 : 60). The second factor is the addition of STPP (0.0, 0.1, 0.2%). Data was analyzed using ANOVA level 5%. If there was a difference, the process continues with the DMRT Test 5%. The results of the study is the proportion of fish meat : sago flour (60 : 40) and the addition of 0.2% STPP was the milkfish bonggolan with the optimal treatment. In this treatment obtained a water content of 51.55%, ash content of 2.67%, protein content of 7.66%, fat content of 2.15%, hardness of 199.87 gf, springiness of 11.33 mm, and organoleptic tests showed the value of color 3.96 (neutral), aroma 4.24 (like), taste 4.08 (like), and texture 4.28 (like).